2020
DOI: 10.3892/ol.2020.12268
|View full text |Cite
|
Sign up to set email alerts
|

Long‑term model of colitis‑associated colorectal cancer suggests tumor spread mechanism and nature of cancer stem cells

Abstract: Although chemical-induced animal models of colorectal cancer (CRC) suggest a lot about the disease, more efforts are required to establish metastasis models. Azoxymethane (AOM) and dextran sodium sulfate (DSS)-treated (AOM/DSS) Crl:CD-1 mice were sacrificed after 10 or 20 weeks in our previous study, and most colon tumors exhibited intramucosal adenocarcinomas. Our observations were extended until 30 weeks to study a colitis-associated advanced CRC mouse model, and explore whether linker threonine-phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…No diffuse inflammation was observed in the colonic mucosal of CAC-induced mice, even though it was reported that signs of diffuse inflammation can appear as early as third to fourth weeks after treatment[ 42 ]. Furthermore, compared to a prior study, where submucosal tumor infiltrations were sporadically seen in 20%–24% of AOM-DSS mice at week ten, the percentage of CAC-induced mice with tumors in this study was considered high[ 43 ]. The selection of the mouse strain may have affected the percentage of tumor occurrence because different strains of mice have varying susceptibilities.…”
Section: Discussionmentioning
confidence: 84%
“…No diffuse inflammation was observed in the colonic mucosal of CAC-induced mice, even though it was reported that signs of diffuse inflammation can appear as early as third to fourth weeks after treatment[ 42 ]. Furthermore, compared to a prior study, where submucosal tumor infiltrations were sporadically seen in 20%–24% of AOM-DSS mice at week ten, the percentage of CAC-induced mice with tumors in this study was considered high[ 43 ]. The selection of the mouse strain may have affected the percentage of tumor occurrence because different strains of mice have varying susceptibilities.…”
Section: Discussionmentioning
confidence: 84%
“…Despite these age-dependent changes, there are very few intervention studies on old mice. One recent study investigated the effect of the duration of tumor development post-tumor induction with AOM, where the mice were in the longest cohort at around 9-months-old at the time of sacrifice [14], which still only corresponds to ~35 years of age in humans [7], while the median age at diagnosis for colon cancer is 67 years [10].…”
Section: Discussionmentioning
confidence: 99%
“…Cross sections were stained with hematoxylin and eosin (H & E) for pathological evaluation. Because AOM/DSS-induced murine CAC exhibits extensive pathological changes from focal inflammation to carcinomas in situ, occasionally, submucosal tumor infiltration depending on the mouse strain, dose of AOM/DSS, and duration of treatment [ 60 , 61 ], pathological changes was evaluated and scored based on the number of inflammatory cells, decrease in goblet cells, reactive atypia/dysplasia, and submucosal tumor infiltration (0, negative; 1, weak; 2, moderate; and 3, strong). These criteria represent major pathological changes for AOM/DSS-induced CAC.…”
Section: Methodsmentioning
confidence: 99%
“…While atypia represents benign cellular abnormalities, dysplasia describes neoplastic events [ 63 ]. Finally, submucosal tumor infiltration is often relevant to lymphatic metastasis [ 61 , 64 ].…”
Section: Methodsmentioning
confidence: 99%